Spectroscopic studies on the enhanced radiation with high Z rare gas seeding for mitigating divertor heat loads in LHD plasmas. (May 2019) - Suzuki, C.; Mukai, K.; Masuzaki, S.; Kobayashi, M.; Peterson, B.J.; Akiyama, T.; Murakami, I.; ,
Highlights: Ions with M-shell outermost electrons dominantly contribute to the radiation enhanced by the Kr seeding. Recombining plasma components are unignorable to explain the measured line intensity ratio of Kr 25+ . A combination of Kr and Ne seedings is possibly useful for more enhanced radiation. Abstract: We have measured extreme ultraviolet (EUV) and soft X-ray emission spectra of krypton (Kr) ions in the Large Helical Device (LHD) plasmas with Kr gas seeding intended for mitigating divertor heat loads. Several isolated lines or quasi-continuum bands from ion stages in the range of Kr 5+ –Kr 25+ have been identified in a variety of wavelength ranges. The time trends of the line intensities indicate major contributions of ions with M-shell ( n = 3) outermost electrons to the enhanced total radiation in the region closer to the core plasma. A line intensity ratio analysis for Kr 25+ implies an unignorable contribution of the recombining component for the emissivity from this ion stage. A difference between the trends of neon (Ne) and Kr is also observed in a discharge with a combination of Kr and Ne seedings intended for more effective radiation enhancement.